Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.21873/cgp.20147
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA 362-3p Reduces hERG-related Current and Inhibits Breast Cancer Cells Proliferation

Abstract: Background/Aim: hERG potassium channels enhance tumor invasiveness and breast cancer proliferation. MicroRNA (miRNA) dysregulation during cancer controls gene regulation. The objective of this study was to identify miRNAs that regulate hERG expression in breast cancer. Materials and Methods: Putative miRNAs targeting hERG were identified by bioinformatic approaches and screened using a 3'UTR luciferase assay. Functional assessments of endogenous hERG regulation were made using whole-cell electrophysiology, pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 38 publications
0
20
0
Order By: Relevance
“…Furthermore, some studies have reported its pivotal effect on tumors. Assiri et al [25] revealed that miR-362-3p mediates the transcriptional regulation of the human ether-ago-go-related gene (hERG) and is associated with survival in breast cancer [25]. Christensen's study concluded that miR-362-3p may be a novel prognostic marker for colorectal cancer, and this study hypothesizes that the positive effects of augmented miR-362-3p expression may in part be mediated through hypothetical target protein 1 (PTPN1) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, some studies have reported its pivotal effect on tumors. Assiri et al [25] revealed that miR-362-3p mediates the transcriptional regulation of the human ether-ago-go-related gene (hERG) and is associated with survival in breast cancer [25]. Christensen's study concluded that miR-362-3p may be a novel prognostic marker for colorectal cancer, and this study hypothesizes that the positive effects of augmented miR-362-3p expression may in part be mediated through hypothetical target protein 1 (PTPN1) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Through bioinformatics analysis, we found that miR-338-3P and miR-362-3P may be downstream target genes of SBF2-AS1. The tumour suppressor genes miR-338-3P-32 32 , 33 and miR-362-3P 34 , 35 are downregulated in many tumours such as ESCC. In this study, RIP and RNA-pull down experiments showed that SBF2-AS1 could directly target miR-338-3P and miR-362-3P, which confirmed the results of bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 99%
“…In gastric cancer, miR‐362‐3p is highly expressed and promotes the migration and invasion of gastric cancer cells by targeting CD82 22 . However, in renal cell carcinoma, breast cancer, lung adenocarcinoma, and colorectal cancer, miR‐362‐3p are all under‐expressed, and inhibit various biological behaviors of cells by regulating hERG, E2F1, USF2, and PTPN 8,9,23–25 . In CC, low expression of miR‐362‐3p is associated with poor prognosis, 11 and miR‐362‐3p inhibits proliferation through MCM5 and other targets 10 .…”
Section: Discussionmentioning
confidence: 99%
“…22 However, in renal cell carcinoma, breast cancer, lung adenocarcinoma, and colorectal cancer, miR-362-3p are all under-expressed, and inhibit various biological behaviors of cells by regulating hERG, E2F1, USF2, and PTPN. 8,9,[23][24][25] In CC, low expression of miR-362-3p is associated with poor prognosis, 11 and miR-362-3p inhibits proliferation through MCM5 and other targets. 10 This may be the reason why the effect of miR-362 mimics is not weaker than siBAP on cell biological behaviors in our research results.…”
Section: Discussionmentioning
confidence: 99%